Implementasi Jenis Sanksi bagi Anggota TNI Pelaku Kejahatan Ditinjau dari Peraturan Berlaku - Ritonga, Nurliana; Ismail, Ismail; Ompusunggu, Frandika Ferianto; Hutama Hutabarat, Dany Try (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Any activities or actions of members of the TNI that violate law, order and authority and cause public unrest will be immediately subject to sanctions. If a criminal case is not immediately resolved in accordance with applicable law, it is very detrimental to the victim, the perpetrator (in this case the TNI members themselves) and the unit in general that develops personnel. Crime is a crime that is prohibited by laws and regulations, as well as threats (punishments) in the form of certain crimes against people who violate the prohibition. Indonesian law states that no citizen is immune from the law, even if the crime was committed by a citizen or member of the TNI. Every member of the TNI must have a disciplined attitude and carry out the task of being a role model for the surrounding community, but the TNI is also an ordinary human being who can sometimes commit despicable and despicable personal actions. Any activities or actions of members of the TNI that violate law, order and authority and cause public unrest will be immediately subject to sanctions. If a criminal case is not immediately resolved in accordance with applicable law, it is very detrimental to the victim, the perpetrator (in this case the TNI members themselves) and the unit in general that develops personnel. Crime is a crime that is prohibited by laws and regulations, as well as threats (punishments) in the form of certain crimes against people who violate the prohibition. To speak of evil, the following elements must be present: 1. Purpose. 2. Error (trick or error). 3. Breaking the law s. 4. Prohibited or obligatory actions that are punishable by a criminal. 5. Other objective elements, such as time, place and circumstances. Criminal sanctions are a conflict of pain imposed by the state on the convict.